PENGARUH VIRAL MARKETING, PROMO GRATIS ONGKIR, DAN SISTEM COD TERHADAP KEPUTUSAN PEMBELIAN PADA TIKTOK SHOP (Studi Kasus Pada Mahasiswa Manajemen Universitas PGRI Semarang) - Mitha Arum Sari; Lilis Rahmawati, Rauly Sijabat (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
The aim of this research is to determine the influence of viral marketing, free shipping promos and the COD system on purchasing decisions at the TikTok Shop. Quantitative research methodology was used in this research. Primary data collected through questionnaires was used in this research. There were 50 respondents from management students at PGRI University Semarang consisting of the research sample. The analysis method uses SPSS version 25 software and multiple linear analysis. Viral marketing does not significantly influence purchasing decisions, according to the data, which has a tcount of 1,494 and ttable 1,677. The free shipping promotion does not significantly influence purchasing decisions, according to data which has a tcount of 0.774 and ttable of 1.677. The COD system, with a tcount of 3,556 and ttable 1,677, significantly influences consumers' purchasing decisions.